Analysis of Human Resource Capability in Mastering Soft Skills for Performance Improvement - Asyhari, Sri Irmayanti; Karyadi, Sugeng; Hsb, Khoirun Nisa; Munizu, Musran; Wiryawan, Dedik (International Journal Of Education, Social Studies, And Management (IJESSM), 2025)
Human resources are one of the most valuable company assets compared to other assets because they are the primary driving force behind the organization's operations. Human resources must be managed optimally and continuously, given extra attention and their rights fulfilled. Furthermore, human resources are a vital partner for the business in achieving organizational goals. Companies must also improve their human resources competencies in line with globalization. The purpose of this research is to analyze human resources capability in mastering soft skills for performance improvement. To present the analysis in this study, literature research was used. This literature research uses secondary sources such as books and related research journals for a deep analysis. The results of the research analysis summarize that mastering soft skills in human resources capability is crucial for performance improvement because they influence how individuals interact, solve problems, and adapt, driving efficiency, productivity, collaboration, achieving organizational goals, and making employees include communication, teamwork, emotional intelligence, problem-solving, time management, and leadership.